2019
DOI: 10.2147/tcrm.s195010
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk factors of postoperative pulmonary complications after minimally invasive anatomic resection for lung cancer</p>

Abstract: PurposeThis study investigated the perioperative risk factors of postoperative pulmonary complications (PPCs) after minimally invasive anatomic resection for lung cancer.Patients and methodsWe retrospectively reviewed the data from medical records of 729 lung cancer patients undergoing minimally invasive anatomic lung resections between January 2017 and December 2017. Univariate and binary logistic regression analyses were performed to select the independent risk factors for PPCs during the patient’s postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…[8][9][10] Obesity, as a risk factor for pulmonary complications after spinal surgery, was also revealed to be a risk factor of PE after spinal surgery. 6,[28][29][30][31] Besides, hypertension and cardiovascular diseases were also identified as the risk factors of complication after spinal surgery. 8,[32][33][34][35] In the present study, we retrospectively evaluated elderly patients (≥ 65 years) diagnosed with VCFs who underwent PVP or PKP surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Obesity, as a risk factor for pulmonary complications after spinal surgery, was also revealed to be a risk factor of PE after spinal surgery. 6,[28][29][30][31] Besides, hypertension and cardiovascular diseases were also identified as the risk factors of complication after spinal surgery. 8,[32][33][34][35] In the present study, we retrospectively evaluated elderly patients (≥ 65 years) diagnosed with VCFs who underwent PVP or PKP surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Complications such as pulmonary complications after minimally invasive surgery could lead to a straight decline in the survival rate of elderly patients with VCFs [15][16][17]. Previous studies have showed that obesity was considered as risk factor for pulmonary complications after spinal surgery [2,29,30]. Obesity has been illustrated to reduce lung volume and change ventilation pattern, which is more likely to occur in the elderly patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pulmonary complications are still present in ~25% of patients. These occur, especially in smokers, patients with COPD, obese, male gender, and those aged over 50 years (29). Pneumonia and atelectasis were the most common complications, with an incidence of ~13%.…”
Section: Complicationsmentioning
confidence: 99%